2007
DOI: 10.1177/1743872107081431
|View full text |Cite
|
Sign up to set email alerts
|

“This is the Authority. This Planet is Under Our Protection” — An Exegesis of Superheroes' Interrogations of Law

Abstract: Swinburne Research Bank http://researchbank.swinburne.edu.au Bainbridge, J. (2007). 'This is the Authority: this planet is under our protection': an exegesis of superheroes' interrogations of law Originally published in Law, Culture and the Humanities, 3(3); 455-476

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 2 publications
(2 reference statements)
0
12
0
1
Order By: Relevance
“…Unlike their fictional counterparts, however, this study found that RLSHs lack the kinds of fantastic origin stories featuring cosmic rays, radiation or magic artefacts found in comic books and in film (see Bainbridge, 2007). Nevertheless, fictional superheroes in many cases had directly or indirectly inspired their decisions to become RLSHs.…”
Section: Becoming a Real-life Superheromentioning
confidence: 62%
“…Unlike their fictional counterparts, however, this study found that RLSHs lack the kinds of fantastic origin stories featuring cosmic rays, radiation or magic artefacts found in comic books and in film (see Bainbridge, 2007). Nevertheless, fictional superheroes in many cases had directly or indirectly inspired their decisions to become RLSHs.…”
Section: Becoming a Real-life Superheromentioning
confidence: 62%
“…See Kamir (2005) and Manderson (2011). For a discussion of Daredevil as lawyer and superhero see Bainbridge (2007) and Sharp (2012). For an analysis of She-Hulk, see Mitchell (2015).…”
Section: 'The Only Morality In a Cruel World Is Chance': Law Procedumentioning
confidence: 99%
“…82 In the westerns, in order to civilise the Wild West, there is a need to 'print the legend' rather than the truth. Yet, whilst The 79 See Bainbridge (2007) and Sharp (2012).…”
Section: Law Compassion and The Non-hero: Batman As A Typology Of Chmentioning
confidence: 99%
“…Nature and the purpose of humanity were determined within God's plan for the universe; just and proper human laws needed to be in line with the natural laws of God's plan. 1 Thus, in the medieval period:…”
Section: Batman's Modernismmentioning
confidence: 99%